Effects of intervention on lifestyle changes among coronary artery disease patients: A 6‐month follow‐up study. Issue 4 (17th April 2022) - Gaudel, Pramila; Neupane, Subas; Koivisto, Anna‐Maija; Kaunonen, Marja; Rantanen, Anja
Abstract: Aim: The main aim of the study was to investigate the effects of a nurse‐led lifestyle‐related risk factor modification intervention on multiple lifestyle behaviours among coronary artery disease patients over six months. Design: A pre‐test post‐test control group design was conducted in a single clinical centre in Nepal. Methods: A total of 224 eligible patients were randomly assigned to either the usual care group or the intervention group at baseline. The lifestyle intervention consisted of a brief counselling session supplemented with informational leaflets. Standard questionnaires were used to collect self‐reported data from patients on multiple lifestyle behaviours: diet, physical activity, adherence to medication, stress, body mass index, smoking and alcohol consumption. General linear model repeated measure analysis was used to estimate the effect of intervention. Results: A statistically significant effect of study group‐by‐time interaction for diet, adherence to medication, physical activity, and perceived stress was found at 6‐month follow‐up. Overall, greater improvement in lifestyle habits was found in the intervention group compared with the control group at 6‐month follow‐up.